Inhaled Mannitol as a Therapeutic Medication. Issue 5 (September 2016) - Daviskas, Evangelia; Anderson, Sandra D.
Abstract : Airway diseases, such as asthma, bronchiectasis, and cystic fibrosis (CF), are characterized by excessive secretion of mucus that fails to clear from the airways due to insufficient hydration at the airway surface. Failure to clear this mucus results in chronic cough, persistent inflammation, recurrent infective exacerbations, a poor quality of life, and an increased risk of morbidity and mortality. Inhaled dry powder mannitol, being an osmotic agent, improves hydration at the airway surface, which in turn improves the physical properties of mucus and facilitates its clearance. These changes once sustained have been shown to improve or at least sustain lung function, reduce mucus plugging and biofilm formation, reduce the incidence of exacerbations, increase the time to first exacerbation, reduce antibiotic use, and improve the quality of life. Long-term clinical benefits have been shown in patients with bronchiectasis and CF. Currently, inhaled mannitol has regulatory approval to be an add-on treatment in patients with CF. In addition to the clinical benefits, the fast delivery of mannitol to the airways and the fact that mannitol can be transported anywhere makes it an attractive treatment as it can reduce the burden of treatment. Inhaled mannitol could potentially benefit all hypersecretory diseases that have reduced hydration leading to compromised mucus clearance and to airway disease.